A cross-national analysis of sociodemographic variation in suffering across 22 countries - Richard G. Cowden; Zhuo Job Chen; Renae Wilkinson; Dorota Weziak-Bialowolska; Thomas Breedlove; Craig Gundersen; Koichiro Shiba; R. Noah Padgett; Byron R. Johnson; Tyler J. VanderWeele (Communications Medicine)
Abstract Background Suffering has been identified as an important public health issue worthy of closer attention. This preregistered study takes an initial step toward developing an epidemiology of suffering by exploring the distribution of suffering in 22 countries and testing for sociodemographic disparities in suffering. Methods Using nationally representative data from the first wave of the Global Flourishing Study (N = 202,898), we estimated the proportion of people who endorsed some/a lot of suffering in each country. Variation in proportions of suffering across the categories of 9 sociodemographic characteristics (age, gender, marital status, employment status, years of education, immigration status, frequency of religious service attendance, religious affiliation, racial/ethnic identity) were estimated separately for each country. We aggregated country-level estimates of suffering for specific sociodemographic categories using random effects meta-analyses. Results We find that the proportion of country-specific populations experiencing suffering varies considerably, ranging from 0.24 (Poland) to 0.60 (Türkiye). Country-level results provide evidence of cross-national heterogeneity in suffering for all sociodemographic categories, although variation is greater for some categories than others. Meta-analytic results support differences in suffering based on marital status, employment status, and years of education across the countries, with the highest suffering observed among those who have separated from their spouse, are either unemployed and looking for a job or endorse the none of these/other employment status category, and have completed 8 or fewer years of education. Conclusions Suffering varies across countries and sociodemographic categories. Our findings lay the foundation for population-level monitoring of suffering and a population health agenda to address suffering among vulnerable subpopulations.